L’approche patrimoniale comme outil d’analyse et de mise en œuvre du projet de territoire en Italie - Maria Rita Gisotti (Projets de Paysage)
The article offers a reflection on the territory-based approach to landscape planning in Italy. The notion upon which this scientific approach is based is that of territorial and landscape heritage, a complex set of cultural and functional values. The article describes the principal paradigms in the heritage approach and the way it is applied in the Tuscan landscape plan. Based on a case study, the article concludes by suggesting further ideas for deploying such instruments aimed at shifting from a static to a dynamic preservation of the landscape.